Drug information by public health and regulatory institutions: Results of an 8-country survey in Europe - Formoso, Giulio; Font-Pous, Maria; Ludwig, Wolf-Dieter; Phizackerley, David; Bijl, Dick; Erviti, Juan; Pospíšilová, Blanka; Montastruc, Jean Louis (Health policy (Amsterdam, Netherlands), 2017)
PURPOSE: To evaluate the framework of drug information produced by public health and regulatory institutions in Europe. MATERIALS AND METHODS: We carried out a short survey asking editors of ISDB bulletins of the European region to indicate the main sources of drug information provided by public health and regulatory authorities in their countries, the specific kind of information produced and their opinions about strengths and weaknesses of such information. The availability of evaluations about the added therapeutic value of drugs and of tools facilitating the implementation of such information were particularly addressed and checked on the websites of those institutions. RESULTS: Answers pertaining to eight countries were available. Regulatory information and safety alerts are generally available, but just UK and Germany stand out by showing quite an advanced framework of evidence-based, comparative drug information for health professionals, decision-makers and for the general public. National plans to implement evidence-based drug information seem lacking. CONCLUSION: More efforts are warranted to develop sharp formats to make evidence-based drug information easier to access, understand and put in context, showing the place in therapy of medicines and their added therapeutic value. Harmonization of different sources, also at European level, would be important to favor their access and limit dispersion. Appropriate tools and specific plans are then necessary to favor implementation of information materials.
Keywords: Drug Information Services; sběr dat; Consumer Product Safety; Europe; Public Health; informační služby o lécích; Evropa; průzkumy a dotazníky; Public health institutions; Prescription Drugs; Product Surveillance, Postmarketing; vládní regulace; léky na předpis; Evidence-based drug information; Adverse Drug Reaction Reporting Systems; Data Collection; Humans; systémy pro sběr zpráv o nežádoucích účincích léků; Surveys and Questionnaires; Government Regulation; Added therapeutic value; spotřebitelská bezpečnost produktů; Medicines regulatory agencies; postmarketingový dozor; veřejné zdravotnictví; lidé